Interaction of Nanocomposites Based on the FemOn–SiO2 System with an Electromagnetic Field in an Ultra-Wide Frequency Range - Kamil G. Gareev (Magnetochemistry, 2020)
The article describes the interaction of nanocomposites based on the FemOn–SiO2 system with an electromagnetic field (radiation) in an ultra-wide frequency range 0–1021 Hz. The development of the technique based on the sol–gel method for producing nanocomposites is described, which made it possible to achieve superparamagnetic properties in combination with low toxicity when used in vivo and in vitro and a high microwave absorption coefficient, which makes it possible to use the obtained nanocomposites in solving a wide range of practical problems. The most effective methods of exposure and threshold levels of the electromagnetic field, the corresponding modifications of the magnetic structure, crystalline structure and microstructure of nanocomposites are determined.